WORLDS, OBJECTS, AND THEORIES OF FICTION - RUSU, Mihai (Studia Universitatis Babeș-Bolyai Philosophia, 2020)
The main aim of this paper is to provide a critical discussion of some key issues concerning the possible-world analysis of fiction. After a review of the most important philosophical questions concerning truth, reference, names and identity, and their bearing on fiction, I outline the possible-world framework, as used by David Lewis (1978) in his analysis, and examine its most important problems. A special interest is granted to the limits of the Lewisian pretense interpretation of fiction that are highlighted by works of cinema. I conclude with an appraisal of the puzzles generated by the attempts to draw borders between and within the worlds of fiction, and emphasize the need for a better mutual understanding of the two perspectives that are essential for a possible-world interpretation of fiction: literary theory and philosophy.